Occupational transitions - Mumbai Archive Project Team (Jio Institute, 2024)
While the Kolis traditionally engaged in fishing or fishing-related businesses, not all members of the community continue these practices in modern times. Pragna Keni comes from a family that sells flowers outside a temple. Despite being part of the Koli community, neither she nor her family have ever been involved in trading or fishing activities.